Occurrence of Legionella in technological water and studies of the total number of bacteria and fungi in indoor air at workplaces where water aerosol is generated - Bożena Krogulska; Renata Matuszewska; Adam Krogulski; Maciej Szczotko; Marta Bartosik; Dorota Maziarka; Radosław Giziński (Nofer Institute of Occupational Medicine, 2014)
Background: The aim of the study was to confirm the fact that technological water is a significant carrier of Legionella, a potential serious threat to the health of operators of mechanical devices generating contaminated water aerosol. Material and Methods: Microbiological analyses of water and indoor air were conducted in 8 different production facilities involved in mechanical processing of glass. The study covered 81 samples of water collected from technical water systems. Isolation of Legionella and the determination of total number of microorganisms were processed according to PN-EN ISO 11731-2:2008E and PN-EN ISO 6222:2004P, respectively. Air samples were collected using air samplers and total numbers of bacteria and fungi were determined. Results: The studies of process water, indicated the presence of Legionella in 27.2% of collected samples. These bacteria were present in both closed and open process water reservoirs at 10 cfu/100 ml to 2.9×104 cfu/100 ml. The count of other associated bacteria exceeded 103 cfu/ml. All strains isolated from Legionella-positive samples were identified as L. pneumophila SG 2-14. In 5 of 8 studied production facilities an increased total number of aerial bacteria and fungi was observed in samples collected in close vicinity of aerosol source. Conclusions: To reduce the number of microorganisms in water it is required to introduce technological water quality monitoring and procedures for the cleaning and disinfecting of mechanical devices generating water aerosol. Med Pr 2014;65(3):325-334